The impact of the COVID-19 pandemic on the psychological distress of parents and children cancer care: A cross-sectional study - Krisnana, Ilya; Rachmawati, Praba Diyan; Nastiti, Aria Aulia; Soares, Domingos; Puspitasary, Novalia (Pediomaternal Nursing Journal, 2025)
Introduction: The current situation of the COVID-19 pandemic has an impact on stress among parents of children with cancer. This uncertain situation can cause psychological distress experienced by parents and can reduce the level of care for children with cancer, it can reduce the cure rate and increase the morbidity rate of children with cancer. The study aimed to analyses the impact of the COVID-19 pandemic on the psychological distress of parents and the treatment of children with cancer. Methods: The research design used was descriptive analytics with a cross-sectional approach. The population in this study were parents of children with cancer living in the Surabaya and East Java areas who lived in a halfway house. Respondents were 78 parents of children with cancer. The children were aged between 2 and 15 years. Selected using the convenience sampling technique for three months (June to August 2022). The independent variable in this study was the level of psychological distress, while the dependent variable was the treatment of children with cancer. The data was obtained using the DASS-21 questionnaire and analyzed using the Spearman Rank Correlation test with α = .05. Results: The results of the study showed that there was an impact of the COVID-19 pandemic on psychological distress [(stress P-value = .002; r = .341); (anxiety P-value = .013; r = .281), and depression P-value = .026; r = .252)] and cancer care for children. Conclusion: The COVID-19 pandemic has an impact on the psychological distress of parents and the care of children with cancer. The level of stress experienced by parents should be given further treatment immediately. Keywords: cancer; chronic diseases; COVID-19; pandemic; psychological distress